Outcomes-based commissioning for social care in extra care housing: is there a future?. Issue 2 (5th June 2017) - Smith, Randall; Darton, Robin; Cameron, Ailsa; Johnson, Eleanor K.; Lloyd, Liz; Evans, Simon; Atkinson, Teresa June; Porteus, Jeremy
Abstract : Purpose: The purpose of this paper is to provide an overview of the process of commissioning adult social care services in England. It reflects the literature on commissioning at the strategic level followed by a section on operational or micro-commissioning. The rest of the paper focusses on the emergence of ideas about outcomes-based commissioning (OBC) in the field of adult social care and ends with critical consideration of the effectiveness of OBC in adult social care as applied to support and care provided in extra care housing. Design/methodology/approach: The review of strategic and operational commissioning in adult social care in England (and Scotland in brief) is based on both policy documents and a review of the literature, as are the sources addressing OBC in adult social care particularly in extra care housing settings. Findings: The core of this paper focusses on the challenges to the implementation of OBC in adult social care in the context of provision for residents in extra care housing. Of central importance are the impact of the squeeze on funding, increasing costs as a result of demographic change and the introduction of a national living wage plus the focus on the needs of service users through the idea of person-centred care and resistance to change on the part of adult social care staff and workers in other relevant settings. Originality/value: Addressing the implementation of OBC in adult social care in England in the context of extra care housing.